TB-8 Genetic and molecular properties of long-term proliferating tumorsphere -forming glioma derived cells. (6th December 2021) - Kijima, Noriyuki; Kanematsu, Daisuke; Shofuda, Tomoko; Yoshioka, Ema; Yamamoto, Atsuyo; Handa, Yukako; Fukusumi, Hayato; Katsuma, Asako; Sumida, Miho; Moriuchi, Shusuke; Nonaka, Masahiro; Okita, Yoshiko; et al.
Abstract: Long-term proliferating tumorsphere-forming glioma derived cells (LTP-TS-GDCs) and patient derived xenografts (PDXs) are essential tools for translational research for glioma. However, only small subsets of glioma samples are established as LTP-TS and/or PDXs and little is known about the genetics and molecular properties of LTP-TS -forming GDCs and PDX. In this study, we aim to analyze the characteristics of LTP-TS -forming GDCs and PDXs. We tried primary sphere cultures from 56 glioma patient-derived samples and established 11 LTP-TS-GDCs out of 45 glioblastoma samples and no long-term sphere culture was isolated from grade3 and grade 2 gliomas. LTP-TS-GDCs had self-renewal ability and possessed certain multipotency. However, they significantly less expressed SOX1 FOXG1 and TUBB3, whereas they expressed LGALS1 and EN1 significantly higher than normal neural stem/progenitor cells. In addition, we found that LTP-TS-GDCs shared the same genetic profiles with original patients' tumors. Furthermore, we investigated the genetic differences between the glioma tissues which were successfully established as LTP-TS-GDCs and those which were not. We found that glioma tissues with TERT promotor mutations and triple copy number alteration (CNA) [EGFR, CDKN2A, and PTEN loci] are significantly established as LTP-TS-GDCs. Lastly, we next investigated in vivo characteristics of glioma PDXs. We have injected glioma PDXs lines into immunodeficient mice brains and histopathologically analyzed the characteristics of xenografts. Each xenograft well recapitulated histological features of original patients' tumors and tumor cells remarkably invade through subventricular zone. In conclusion, each LTP-TS-GDCs and PDXs had various gene expression profiles, reflecting intratumoral and interpatient heterogeneities of glioma. In addition, TERT promotor mutations and triple CNA significantly correlated with success rate of LTP-TS-GDCs. These findings will be of use and advance the preclinical and translational researches of glioma.